Elementary preservice teachers’ and elementary inservice teachers’ knowledge of mathematical modeling - Schwerdtfeger, Sara (Kansas State University, 2017)
This study examined the differences in knowledge of mathematical modeling between a group of elementary preservice teachers and a group of elementary inservice teachers. Mathematical modeling has recently come to the forefront of elementary mathematics classrooms because of the call to add mathematical modeling tasks in mathematics classes through the Common Core State Standards (NGACBP & CCSS, 2010). According to Ellis and Berry (2005), the recommendation for teachers to think differently about teaching mathematics includes more comprehensive knowledge of mathematics continuing beyond rote facts, skills, and procedures. Although preservice teachers and inservice teachers vary in teaching experience, their knowledge in mathematical modeling may be similar as, quite possibly, neither had explicit instruction during their elementary education programs. In learning and teaching mathematics, the modeling approach can be useful by directing the focus on creating generalizable and reusable relations rather than solving a particular problem (Doerr & English, 2003). This survey research, tailored design method employed a brief online survey to a convenience sample of preservice and inservice elementary teachers to gain information about their knowledge of mathematical modeling in the elementary school classroom. For the purposes of this research, the definition of mathematical modeling was applying mathematics to real world problems with the purpose of understanding the problem. This study used non-experimental, survey research to determine if there was a statistical significant difference between preservice teachers’ and inservice teachers’ knowledge of mathematical modeling. Independent t-tests were used to determine there was no statistical significant difference in elementary preservice teachers and elementary inservice teachers knowledge of mathematical modeling. Another aspect of this research was to determine if any variables were able to predict the preservice or inservice teachers’ knowledge of mathematical modeling. Multiple regression was used to determine the variables of years of teaching experience, grade level currently taught, or type of school in which teaching occurs did not have any predictor aspects of knowledge of mathematical modeling. ANOVA was used to determine there was no relationship between preservice and inservice teachers’ perceived knowledge of mathematical modeling and their actual knowledge of mathematical modeling
Keywords: Mathematical; Modeling; Elementary; Teachers; Preservice; Mathematics